Learning 3d Geometry Using Geogebra On Students' Mathematical Reasoning Ability - Supriyadi Supriyadi; Loliyana Loliyana; Jody Setya Hermawan; Anisa Anisa; Ika Wulandari Utamining Tias; Fatkhur Rohman; Amrina Izzatika; Syarifatul Muafifah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Along with the development of science and technology (IPTEK) which is increasingly sophisticated, the tools used by educators are not optimal in learning, this can be seen from the lack of student interaction during learning. Students do not have the opportunity to interact with the media used by educators longer. In learning geometry on the material of building space, the level of understanding of students on this material requires visualization. Students feel confused to imagine the shape of the building space. The research method used in this research is descriptive research with a quantitative approach that describes a situation objectively using numbers ranging from data collection, interpretation of the data and the appearance and results. The results of the research that has been done that there is an effect of the implementation of geogebra on learning geometry 3D space building material on the mathematical reasoning ability of students. In addition, the effect of geogebra implementation on learning geometry 3D space building material on mathematical reasoning ability has an influence of 94.9%.